2015
DOI: 10.1159/000367656
|View full text |Cite
|
Sign up to set email alerts
|

Individualized Supplementation of Folic Acid According to Polymorphisms of Methylenetetrahydrofolate Reductase (MTHFR), Methionine Synthase Reductase (MTRR) Reduced Pregnant Complications

Abstract: Objective: This study aimed to detect the genotype distributions and allele frequencies of methylenetetrahydrofolate reductase (MTHFR) C677T, A1298C and methionine synthase reductase (MTRR) A66G polymorphisms of pregnant women in Jiaodong region in China, and to investigate whether folic acid supplementation affect the pregnancy complications. Setting: A total of 7,812 pregnant women from the Jiaodong region in Shandong province in China. Methods: By using Taqman-MGB, 2,928 pregnant women (case group) were tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…For MTHFR C677T mutation in RM patients and in agreement with other studies, no significant ( P > 0.05) association with RM were found [ 29 ]. The general practice of folic acid supplementation during pregnancy seems to be the reason of masking the effect of the MTHFR mutation in RM patients as reported elsewhere [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…For MTHFR C677T mutation in RM patients and in agreement with other studies, no significant ( P > 0.05) association with RM were found [ 29 ]. The general practice of folic acid supplementation during pregnancy seems to be the reason of masking the effect of the MTHFR mutation in RM patients as reported elsewhere [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the first study to examine folate intake from both food and supplements in relation to GDM risk with adjustment for other major dietary factors. We are only aware of two existing studies examining folic acid supplementation before or during pregnancy in relation to GDM risk (19,20); the results were contradictory. The first study was conducted in a hospital in China including 166 women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…The first study was conducted in a hospital in China including 166 women with GDM. It found that women who received folic acid supplementation intervention had a lower risk of developing GDM (19). However, the study excluded women who smoked cigarettes, drank alcohol, had chronic diseases, or took prescription medications during the perinatal period from the intervention group but not from the control group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest that the MTHFR T allele may contribute to the risk of neural-tube defects (NTD), congenital heart defects (CHD), and pregnancy complications. [ 25 28 ] Both heterozygous and homozygous 677C>T genotypes have been found to be associated with elevated plasma Hcy levels. [ 29 , 30 ] Hcy is a biomarker that can be used to identify women at risk of complications and adverse pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%